Timing Tasks Synchronize Cerebellar and Frontal Ramping Activity and Theta Oscillations: Implications for Cerebellar Stimulation in Diseases of Impaired Cognition - Parker, Krystal L. (Frontiers in Psychiatry, 2016)
Timing is a fundamental and highly conserved mammalian capability yet the underlying neural mechanisms are widely debated. Ramping activity of single neurons that gradually increase or decrease activity to encode the passage of time, has been speculated to predict a behaviorally relevant temporal event. Cue-evoked low-frequency activity has also been implicated in temporal processing. Ramping activity and low-frequency oscillations occur throughout the brain and could indicate a network-based approach to timing. Temporal processing requires cognitive mechanisms of working memory, attention, and reasoning which are dysfunctional in neuropsychiatric disease. Therefore, timing tasks could be used to probe cognition in animals with disease phenotypes. The medial frontal cortex and cerebellum are involved in cognition. Cerebellar stimulation has been shown to influence medial frontal activity and improve cognition in schizophrenia. However, the mechanism underlying the efficacy of cerebellar stimulation is unknown. Here we discuss how timing tasks can be used to probe cerebellar interactions with the frontal cortex and the therapeutic potential of cerebellar stimulation. The goal of this theory and hypothesis manuscript is threefold. First, we will summarize evidence indicating that in addition to motor learning, timing tasks involve cognitive processes that are present within both the cerebellum and medial frontal cortex. Second, we propose methodologies to investigate the connections between these areas in patients with Parkinson’s disease, autism, and schizophrenia. We hypothesis that cerebellar transcranial stimulation may rescue medial frontal ramping activity, theta oscillations, and timing abnormalities, thereby restoring executive function in diseases of impaired cognition. These hypotheses could inspire the use of timing tasks as biomarkers for neuronal and cognitive abnormalities in neuropsychiatric disease and promote the therapeutic potential of the cerebellum in diseases of impaired cognition.